2016
DOI: 10.1093/cid/ciw624
|View full text |Cite
|
Sign up to set email alerts
|

Training Community Health Workers to Manage Uncomplicated and Severe Malaria: Experience From 3 Rural Malaria-Endemic Areas in Sub-Saharan Africa

Abstract: Background. Use of community health workers (CHWs) to increase access to diagnosis and treatment of malaria is recommended by the World Health Organization. The present article reports on training and performance of CHWs in applying these recommendations.Methods. Two hundred seventy-nine CHWs were trained for 3–5 days in Burkina Faso, Nigeria, and Uganda, and 19 were certified to diagnose and treat only uncomplicated malaria and 235 to diagnose and treat both uncomplicated and severe malaria. Almost 1 year aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…These results are nonetheless consistent with another study on community health workers' performance conducted in Burkina Faso, Nigeria, and Uganda, where 98% of the tasks were mastered by respondents [15]. They are also consistent with those of a recent observational study conducted in the same context with 14 CBDs, which concluded that they "deliver acceptable quality of care" [16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are nonetheless consistent with another study on community health workers' performance conducted in Burkina Faso, Nigeria, and Uganda, where 98% of the tasks were mastered by respondents [15]. They are also consistent with those of a recent observational study conducted in the same context with 14 CBDs, which concluded that they "deliver acceptable quality of care" [16].…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have shown that the personal characteristics of community health workers can be associated with their performance [8,11,15,27], suggesting that the CBDs to be trained should be carefully selected [11,28]. However, recent reviews reveal that results, particularly with regard to performance compared by type and sex, are not always consistent [12], and that "studies of workers with lower baseline performance showed greater improvements in prescribing medications…, vaccinating children,… and counseling…" [29].…”
Section: Discussionmentioning
confidence: 99%
“…Once CHWs were identified, training was carried out by health staff (Burkina Faso and Uganda) or the investigative team (Nigeria) in sessions that covered theory and practice [8]. Training included diagnosis and recognition of uncomplicated and severe illness with danger signs, counting respiratory rate, diagnosis using RDTs (preparing, reading, recording results), and treatment dosage by age.…”
Section: Methodsmentioning
confidence: 99%
“…Training was evaluated through pre- and post-tests [8]. A total of 31, 40, and 164 CHWs passed all certification exams in Burkina Faso, Nigeria, and Uganda, respectively, and were authorized to diagnose and treat uncomplicated and severe malaria, but in Burkina Faso 19 CHWs failed the severe malaria component necessary for use of rectal artesunate, and were only authorized to diagnose and use ACTs.…”
Section: Methodsmentioning
confidence: 99%
“…In many areas, CHWs have a critical function in allowing health systems to deliver health care in a cost-effective manner [5]. Task-shifting of certain health care tasks to CHWs has been employed in a variety of health programs, such those for tuberculosis and malaria [68]. …”
mentioning
confidence: 99%